Meningkatkan Keterampilan Komunikasi IPA Tertulis Mahasiswa Tadris Fisika dan Biologi IAIN Palangka Raya melalui Bimbingan Teknik - Santiani, Santiani (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
Communication skills are really needed by generations to be able to adapt to developments in the 21st century. Science scientific written communication skills are related to science process skills. Publication of science scientific works must continue to support the development of technology and science. A thesis as a type of scientific work must be published so that it is widely useful. The aim of this technical guidance activity is to improve students' science scientific written communication skills so that they can complete their final assignments well. Activities were carried out using a quasi-experimental research method with a pretest posttest design. The instrument used is a rubric for scientific written communication skills in science which is analyzed using percentage and categorization techniques. The results of the technical guidance show that the scientific written communication skills of Tadris Physics and Biology students at the PMIPA FTIK IAIN Palangka Raya can be improved. Similar activities must continue to be carried out to build the skills and literacy of the 21st century generation.